MECHANISMS OF FINANCIAL SUPPORT FOR THE AGRICULTURAL SECTOR OF THE REPUBLIC OF UZBEKISTAN (European Journal of Economics, Finance and Business Development, 2025)
Agriculture plays a significant role in the development of the national economy in many countries, being one of its leading sectors. The sustainable development of agriculture is vital for providing food security and ensuring the population's well-being. Agriculture is crucial for the country's economic growth, ensuring food security, creating jobs, stimulating economic expansion, improving the foreign trade balance, and strengthening social stability. In this context, the stable and sustainable development of agriculture is essential, and financing for farmers is critical.